Blood lines: intraspecific and interspecific variations in anticoagulant actions of Agkistrodon viperid venoms - Coimbra, Francisco C. P. (2024)
This study investigated the intraspecific and interspecific variability in the venom effects of Agkistrodon viperid snake species and subspecies (eleven venoms total) on plasma clotting times, fibrinogen levels, and fibrin clot strength. Significant delays in plasma clotting time were observed for A. conanti, A. contortrix mokasen, A. contortrix phaeogaster, A. howardgloydi, A. piscivorus leucostoma, and A. piscivorus piscivorus. Notably, the phylogenetically disjunct lineages A. conanti, A. contortrix mokasen, and A. howardgloydi exhibited the most potent anticoagulant effects, indicating the independent amplification of a basal trait. Inhibition assays with the activated clotting enzymes Factors XIa, IXa, Xa, and IIa (thrombin) revealed that FXa inhibition is another basal trait amplified independently on multiple occasions within the genus, but with A. howardgloydi, notably more potent than all others. Phospholipid degradation and zymogen destruction were identified as mechanisms underlying the variability in venom effects observed experimentally and in previous clinical reports. Thromboelastography demonstrated that the venoms did not clot fibrinogen directly but affected fibrin clot strength by damaging fibrinogen and that thrombin was subsequently only able to cleave into weak, unstable clots. The ability to activate Protein C, an endogenous anticoagulant enzyme, varied across species, with some venoms exceeding that of A. contortrix contortrix, which previously yielded the protein diagnostic agent Protac®. Phylogenetic analysis suggested that both fibrinogen degradation and Protein C activation were each amplified multiple times within the genus, albeit with negative correlation between these two modes of action. This study highlights the evolutionary, clinical, and biodiscovery implications of venom variability in the Agkistrodon species, underscoring their dynamic evolution, emphasising the need for tailored clinical approaches, and highlighting the potential for novel diagnostic and therapeutic developments inspired by the unique properties of snake venoms.